ARGUING PRESIDENT SUBIANTO’S NARRATIVE ON OPPOSITION: BETWEEN ANDERSON, MACHIAVELLI, AND BOURDIEU’S CAPITAL - Azzumar Adhitia Santika; Ari Santoso Widodo (Universitas Muhammadiyah Jember, 2026)
President Prabowo Subianto stressed that the concept of opposition originates from Western culture and is not part of Indonesia’s political culture framework, a statement made during his early months as president. To reflect this view, he formed a large cabinet, even appointing a former presidential election rival as a coordinating minister. This observation study re-examines Prabowo’s assertion by analyzing it through Benedict Anderson’s perspective on the concept of Power in Javanese culture, Niccolò Machiavelli’s teachings on political power, and also Pierre Bourdieu's Theory of Capital. The findings reveal that Prabowo’s statement aligns with Anderson’s view, which posits that Power in Javanese culture is absolute, leaving little room for opposition. Similarly, Machiavelli, a prominent Western philosopher, advocates securing power without interference, opposing the concept of opposition to maintain sovereignty. These findings challenge Prabowo’s claim that opposition is solely a Western concept. Furthermore, the authors argue that Prabowo’s political narrative is inseparable from the accumulation of capital he possesses—particularly cultural, social, and symbolic capital—as framed by Pierre Bourdieu’s framework, rather than a genuinely rooted and robust political philosophy. Therefore, we argue that his statement serves as a political public relations strategy to legitimize his expansive cabinet and consolidate power.